Novel cooperative power control game algorithm for cognitive radio systems - CHENG Shi-lun1; YANG Zhen1; ZHANG Hui2 (Tongxin xuebao)
In order to fair optimally allocate the limited cognitive radio resource,a cognitive radio system was developed based on STBC OFDM-CDMA network systems and a novel Nash bargaining solution named NBS of cooperative power control was adopted in this system,the transmitted power was dynamically adapted based on channel conditions,maxi-mal network throughput and power limits.Simulation results show that the novel algorithm can regulate their transmitter powers,fair optimally allocate radio resource.At the same power consumption,the network throughput is thereby im-proved obviously.